The Effect of Leadership Style, Organizational Culture and Motivation on Teacher Performance (Case Study at the Tanwirul Qulub Islamic Education Foundation) - Mohammad Adam Husein; Syaiful Anwar; Galih Dwi Nugraha (CV. Rayyan Dwi Bharata, 2022)
The purpose of this research is to analyze the effect of leadership style on teacher performance at YPI TQ. To analyze the effect of organizational culture on teacher performance at YPI TQ. To analyze the effect of motivation on teacher performance at YPI TQ. To analyze the effect of leadership style, organizational culture and motivation on teacher performance at YPI TQ. The research method used is quantitative. The population in this study are all elements in YPI TQ, from students, teachers, principals and stakeholders. The results showed that the effect of leadership style on teacher performance at YPI TQ was significant.